Inclusive Islamic Boarding School Integrated Education in Indonesia: sn Educational Model, Obstacles, snd Opportunities - A.M. Wibowo; Dwi Istiyani (International Conference on Science, Education, and Technology, 2023)
The inclusive education integrated paradigm in Islamic boarding schools is a recently developed movement in Indonesia. This concept encourages all santris (students) to actively take part in all areas of learning associated with formal schooling within the pesantren. The purpose of this qualitative research is to explain and evaluate the inclusive education integrated model used by the inclusive Islamic boarding school in Keji Village, which combines Islamic boarding school education with formal education, as well as its obstacles and opportunities. To collect data, in-depth interviews, observation, and structured documentation methods were used. This study discovered four findings; (1) The Keji inclusion Islamic boarding school in Keji village was successful in integrating the model of pesantren education with formal education in the form of madrasah ibtidaiyah; (2) the model of inclusive Islamic boarding school education in Keji Village is carried out by employing the "pull-out" and "push-in" educational models in educational implementation; (3) the obstacles experienced in implementing the integration inclusive Islamic boarding school education model include internal obstacles in the form of parenting competencies and teachers who do not have an inclusive educational background and external obstacles related to the operationalization of Islamic boarding schools which so far have relied on pesantren funding through donors; (4) the integration inclusive Islamic boarding school education model in the Keji village has the opportunity to foster trust and social awareness about equality between humans.